Stochastic Dominance Efficiency Analysis of Diversified Portfolios: Classification, Comparison and Refinements - Andrey Lizyayev (Tinbergen Institute, 2010)
For more than three decades, empirical analysis of stochastic dominance was restricted to settings with mutually exclusive choice alternatives. In recent years, a number of methods for testing efficiency of diversified portfolios have emerged, which can be classified into three main categories: 1) majorization, 2) revealed preference and 3) distribution-based approaches. Unfortunately, some of these schools of thought are developing independently, with little interaction or crossreferencing among them. Moreover, the methods differ in terms of their objectives, the information content of the results and their computational complexity. As a result, the relative merits of alternative approaches are difficult to compare. This paper presents the first systematic review of all three approaches in a unified methodological framework. We examine the main developments in this emerging literature, critically evaluating the advantages and disadvantages of the alternative approaches. We also point out some misleading arguments and propose corrections and improvements to some of the methods considered.
Keywords: G11; G15; 330; Stochastic Dominance; Efficient Portfolios; Diversification; Algorithms; Stochastischer Prozess; Risikoaversion; Algorithmus; Portfolio-Management; Theorie